New records of doryctine wasps (Hymenoptera: Braconidae) from Argentina, with the description of Shawius diiorioi Martínez sp. nov. - Martínez, Juan José (Zootaxa, 2016)
New distributional records of the genera Fritziella Marsh, Rhoptrocentrus Marshall and Shawius Marsh are reported. Fritziella plaumanni Marsh, Rhoptrocentrus piceus Marshall and Shawius braziliensis Marsh are newly reported from northern Argentina. Shawius diiorioi Martínez sp. nov. is described and illustrated from central and northern Argentina. The male of Shawius, previously unknown, is described and illustrated for the first time. All species were reared from Fabaceae and Celtidaceae infested by wood boring Coleoptera.